PEMANFAATAN ALAT PENETAS TELUR AYAM BERBASIS ARDUINO SOLUSI CERDAS UNTUK PENINGKATAN KUALITAS PETERNAKAN MASYARAKAT DESA - Hutabarat, Purnama Helena T (LPPM Universitas Insan Pembangunan, 2025)
Efficient and high quality hatching of chicken eggs is the key to increasing the productivity and success of chicken farming. Along with technological developments, the use of automation systems based on Arduino technology has become a promising solution to overcome challenges in the hatching process. This inqure about points to plant and create an Arduino-based chicken egg incubator that can improve hatching quality through automatic control of temperature, humidity and egg rotation. The method used in this design research includes an Arduino-based control system with DHT22 temperature and humidity sensors, as well as heating and cooling actuators. In addition, this system is equipped with an automatically regulated egg rotation mechanism to ensure even heat distribution. The prototype of this tool was tested to demonstrate its performance in maintaining optimal environmental conditions for hatching. Test results show that the Arduino-based chicken egg incubator can maintain temperature and humidity with high accuracy, as well as automate the egg rotation process, which contributes to increasing the hatching success rate. By implementing this technology, farmers can reduce dependence on manual supervision, increase operational efficiency, and obtain more consistent hatching results. The conclusion of this research confirms that the use of Arduino technology in chicken egg incubators offers a smart and effective solution to improve hatching quality, which in turn can support more productive and sustainable chicken farming.